The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1399-3089.2007.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various immunosuppressive monotherapies on survival and histopathology of monkey islet xenografts in rats

Abstract: This study provided evidence for monkey islet survival after transplantation into rats receiving immunosuppressive monotherapy. Basic information on infiltrating cell types may be important in the study of xenograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…published the importance of establishing islet immunoisolation through magnetocapsules [34], but using our device we are achieving immunoprotection as demonstrated by the function of the islets through porcine C‐peptide and reduction in insulin requirements in more than 81% of the patients (more than 50% of patients remain with a reduction greater than 33%), and through low levels of antibodies already reported [20]. Perhaps our results could be improved if we use an immunosuppressive regimen [35]…”
Section: Discussionmentioning
confidence: 83%
“…published the importance of establishing islet immunoisolation through magnetocapsules [34], but using our device we are achieving immunoprotection as demonstrated by the function of the islets through porcine C‐peptide and reduction in insulin requirements in more than 81% of the patients (more than 50% of patients remain with a reduction greater than 33%), and through low levels of antibodies already reported [20]. Perhaps our results could be improved if we use an immunosuppressive regimen [35]…”
Section: Discussionmentioning
confidence: 83%
“…Balamurugan et al (2) described the effect of CsA, FK506 or prednisolone monotherapy on preventing monkey islet graft rejection after xenotransplantation in a rodent model. Histological examination indicated that monkey islets survived in the presence of continuous high-dose of immunosuppressive monotherapy in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Group I (control): Animals were fed standard balanced dietGroup II (steroid-treated animals): Animals were daily injected with prednisolone in a dose of 20 mg/kg for 2 weeks[13] and fed with balanced standard dietGroup III (steroid/barley-treated group): Animals were injected with prednisolone in the same dose and fed with barley mixed with balanced standard diet for 2 weeks. [14] Dose of barley was 53% of available diet for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…Group II (steroid-treated animals): Animals were daily injected with prednisolone in a dose of 20 mg/kg for 2 weeks[13] and fed with balanced standard diet…”
Section: Methodsmentioning
confidence: 99%